Folkloristics without Illusions. Some Thoughts on the Contexts of Folklore Research by Donatas Sauka - Ivanauskaitė-Šeibutienė, Vita (Tautosakos darbai, 2019)
The 90th anniversary of birth of the famous Lithuanian literary scholar and folklorist, professor of the Vilnius University Donatas Sauka (1929–2015) is celebrated in 2019. The article discusses various contexts of the folklore research and academic activities by Donatas Sauka, revealing his own attitude towards folklore as well. Donatas Sauka is rightly placed among the most original and creative Lithuanian folklore researchers. His works and lectures that he gave to the students of the Vilnius University encourage regarding folklore as an integral part of the human life in the traditional community, and emphasize an imperative of grasping the mentality of the folklore creators. According to him, “a collection of folklore, if read intently provides an important source on the social and psychological experience”. Donatas Sauka also merits praise for his unique writing style that combines the research precision and poetic reflection. His most important folklore research works include the monograph Tautosakos savitumas ir vertė (‘Uniqueness and Value of Folklore’, 1970) and the textbook for students Lietuvių tautosaka (‘Lithuanian Folklore’, 1982). The current text rests on the posthumous edition of Donatas Sauka’ diaries and recollections Apie laiką ir save (‘On Time and Myself’, 2019), in which the author remembers and evaluates his personal experiences and those of an entire generation of the Lithuanian intellectuals living under the Soviet occupation, submits auto-commentaries for his books, and reveals details on his research work.